Physical activity instruction of older adults - Rose, Debra J. (Champaign, IL Human Kinetics, 2019)
Physical Activity Instruction of Older Adults, Second Edition, is the most comprehensive text available for current and future fitness professionals who want to design and implement effective, safe, and fun physical activity programs for older adults with diverse functional capabilities. Along with an updated review of the research and literature, the second edition introduces a new chapter on the concept of whole-person wellness. It offers strategies for integrating the six dimensions of whole-person wellness (physical, emotional, intellectual, vocational, spiritual, and social) into health promotion and physical activity programs for older adults. This cohesive blend of theory, practical content, and detailed instruction is divided into four parts, each of which addresses one or more of the nine training modules that comprise International Curriculum Guidelines for Preparing Physical Activity Instructors of Older Adults, the expert-developed guidelines on which this text is based: Part I presents an overview of the physiological aspects of aging and the field of gerokinesiology to help readers understand the psychosocial and cognitive benefits derived from regular physical activity; Part II leads readers through the process of conducting preexercise health screenings and assessments, providing meaningful feedback to clients, evaluating program outcomes, and helping clients develop short- and long-term behavioral goals; Part III emphasizes programming principles and training methods that will facilitate the development of well-rounded and effective exercise programs. It includes specific activities for engaging older adults mentally, emotionally, socially, and spiritually along with myriad dynamic and static flexibility exercises to address joint and muscle flexibility, muscle strength, balance, mobility, endurance, and power; Part IV focuses on the teaching, motivation, communication, and leadership skills that are necessary for creating effective and safe programs for older adults, with or without specific medical conditions. The text also offers a variety of features devised to enhance reader understanding and learning retention. Chapters begin with a list of objectives to familiarize readers with the key concepts they will learn, and each chapter concludes with thought-provoking study questions and practical application activities to help readers use the information with real-world scenarios to prepare them to design well-rounded physical activity programs. Other student-friendly elements include chapter summaries and key terms. The content is supplemented with photos, figures, and tables, making the book interesting and visually appealing. Physical Activity Instruction of Older Adults, Second Edition, offers students and fitness professionals a contemporary approach that embraces a comprehensive wellness framework for designing health promotion and physical activity programs for older adults.
Part I. Overview of Aging and Physical Activity -- Chapter 1. The Field of Gerokinesiology / Debra J. Rose and Dawn A. Skelton ; Demographics of Older Adults ; Benefits of Physical Activity ; Defining Old Age ; Gerokinesiology: An Expanding Field of Study ; Curriculum Development ; Later Life Training Curricula: The Gold Standard for Instructor Training? ; Career Opportunities ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 2. Predictors of Successful Aging / Debra J. Rose ; Biological Theories of Aging ; Psychological Theories of Aging ; Sociological Theories of Aging ; Models of Successful Aging ; Physical Activity as a Determinant of Successful Aging ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 3. Psychological and Sociocultural Aspects of Physical Activity for Older Adults / Kathleen S. Wilson ; Aging Stereotypes ; Psychosocial Benefits of Physical Activity ; Promoting Physical Activity ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 4. Physiological Aspects of Aging / Priscilla G. MacRae ; Cardiovascular Function ; Respiratory Function ; Muscle Function ; Skeletal Function ; Nervous System Function ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Part II. Screening, Assessment, and Goal Setting -- Chapter 5. Preexercise and Health Screening / Debra J. Rose ; Preexercise Screening ; Screening Steps ; Additional Screening Tools ; Implications for Program Design and Management ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 6. Physical and Functional Assessments / C. Jessie Jones and Roberta E. Rikli ; Functional Fitness Framework ; Considerations for Test Selection and Evaluation ; Recommended Assessment Tools ; Guidelines for Group Physical Performance Testing ; Interpreting Test Results ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 7. Goal Setting and Behavioral Management / Sara Wilcox and Abby C. King ; Factors Influencing Older Adults' Exercise Participation ; Theoretical Frameworks for Behavior Change ; Physically Active Lifestyles ; Implications for Program Design and Management ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Part III. Core Program Principles and Training Methods -- Chapter 8. Important Considerations When Designing Exercise Programs for Older Adults / Debra J. Rose ; Heterogeneity of Older Adults ; Optimizing Physical Function Through Exercise ; Exercise Principles for Program Design ; Specific Exercise Principles for Older Adults ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 9. Whole-Person Wellness for Successful Aging / Janis M. Montague, Debra J. Rose, and Judy Aprile ; Wellness: A Change in Perspective and Perception ; Defining Wellness: A Historical Perspective ; Whole-Person Wellness: A Comprehensive Perspective ; Whole-Person Wellness and Successful Aging: A Winning Combination ; Defining the Dimensions of Wellness ; Applying the Dimensions of Wellness ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 10. Principles of the Warm-Up and Cool-Down / Mary Ann Kluge ; Warming Up ; Goal Setting ; Assessing Participant Readiness ; Increasing the Challenge ; Engaging Participants Socially and Emotionally ; New Warm-Up Strategies ; Cooling Down ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 11. Flexibility Training / Debra J. Rose ; Age-Associated Changes in Flexibility ; Types of Stretching Techniques ; Incorporating Flexibility Training Into the Exercise Program ; Examples of Flexibility Exercises ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 12. Resistance Training / Joseph Signorile ; Benefits of Resistance Training ; Principles of Resistance Training ; Training Variables ; Resistance Training Conditions and Modalities ; Resistance Training for Older Adults ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 13. Aerobic Endurance Training / Susie Dinan-Young and Dawn A. Skelton ; Benefits of Aerobic Endurance Training for Older Adults ; Principles and Considerations for Aerobic Endurance Training ; Variables for Aerobic Endurance Training ; Training Precautions and Considerations ; Implications for Program Design and Management ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 14. Balance and Mobility Training / Debra J. Rose ; Age-Associated Changes in Balance and Mobility ; Balance and Mobility Exercises ; Manipulating the Challenge in a Group Setting ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Part IV. Program Design, Leadership, and Risk Management -- Chapter 15. Applying Movement Analysis and Motor Learning Principles to Program Design / Debra J. Rose ; Nervous and Musculoskeletal System Changes and Motor Skill Learning ; Movement Analysis of Skills ; Motor Learning Principles for the Physical Activity Instructor ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 16. Teaching and Leadership Skills / Helen Hawley-Hague and Susie Dinan-Young ; Developing Your Leadership Style ; Developing Your Instructional Methods, Techniques, and Strategies ; Advancing Your Instructional Skills and Strategies ; Developing Your Leadership Skills ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 17. Exercise Considerations for Medical Conditions / Matthew J. Peterson ; Cardiovascular Conditions ; Pulmonary Disorders ; Diabetes ; Musculoskeletal Conditions ; Neurological and Cognitive Conditions ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Chapter 18. Legal Standards, Risk Management, and Professional Ethics / Debra J. Rose ; The Law and the Physical Activity Instructor ; Risk Management Plans ; Ethical Guidelines for the Physical Activity Instructor ; Summary ; Key Terms ; Recommended Reading ; Study Questions ; Application Activities -- Appendix A. International Curriculum Guidelines for Preparing Physical Activity Instructors of Older Adults -- Appendix B. IDEA Code of Ethics for Personal Trainers -- Appendix C. IDEA Code of Ethics for Group Fitness Instructors.
Includes bibliographical references
Keywords: Physical education for older people; Aging -- Physiological aspects